2012
DOI: 10.1371/journal.pone.0034902
|View full text |Cite
|
Sign up to set email alerts
|

Association of Spermatogenic Failure with the b2/b3 Partial AZFc Deletion

Abstract: Infertility affects around 1 in 10 men and in most cases the cause is unknown. The Y chromosome plays an important role in spermatogenesis and specific deletions of this chromosome, the AZF deletions, are associated with spermatogenic failure. Recently partial AZF deletions have been described but their association with spermatogenic failure is unclear. Here we screened a total of 339 men with idiopathic spermatogenic failure, and 256 normozoospermic ancestry-matched men for chromosome microdeletions including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
4
21
3
Order By: Relevance
“…In the non-Spanish cohort, consistent with the high proportion of North African patients (53.2%) included, AZF deletions were mostly found on hgr E, which is seemingly more prone to Y microdeletions. 28,29 Moreover, the deletion frequency reported in idiopathic AZ and SOZ men (9.09 and 5.5%) in Moroccan population 28 is consistent with our findings in non-Spanish idiopathic AZ and SOZ men (10.7% and 6.9%, respectively). The prevalence of Y microdeletions in our study population (3.3%) is in line with the overall data presented in the literature (3.5%, according to a recent meta-analysis 30 ).…”
Section: -124supporting
confidence: 91%
See 1 more Smart Citation
“…In the non-Spanish cohort, consistent with the high proportion of North African patients (53.2%) included, AZF deletions were mostly found on hgr E, which is seemingly more prone to Y microdeletions. 28,29 Moreover, the deletion frequency reported in idiopathic AZ and SOZ men (9.09 and 5.5%) in Moroccan population 28 is consistent with our findings in non-Spanish idiopathic AZ and SOZ men (10.7% and 6.9%, respectively). The prevalence of Y microdeletions in our study population (3.3%) is in line with the overall data presented in the literature (3.5%, according to a recent meta-analysis 30 ).…”
Section: -124supporting
confidence: 91%
“…The remaining three b2/b3 deletion carriers belonged to hrgs C,F,G,H,I, which is a frequent Y hgr in Moroccan population for which b2/b3 deletion has been recently reported in association with male infertility. 28,29 The significant association observed indicates a Y background-dependent deleterious effect of b2/b3 on spermatogenesis.…”
Section: -124mentioning
confidence: 89%
“…It varies from 2.1 to 12.5 % among all cases, and from 0 to 10.2 % among normozoospermic controls [69]. In a conflicting report by Eloualid et al, [65] they have reported that gr/gr deletions occur at similar frequencies of 5.83 and 6.25 % in patient and control populations respectively, suggesting that these deletions are not associated with spermatogenic failure.…”
Section: The Azfb (P5/proximal-p1) Regionmentioning
confidence: 95%
“…However, the prevalence of the b1/b3 deletion in the human population is very low and its frequency varies, with only 18 deletions published to date [65]. Its effect on spermatogenesis is unknown [66].…”
Section: The Azfb (P5/proximal-p1) Regionmentioning
confidence: 99%
See 1 more Smart Citation